New Business Opportunities for Latin American Small and Medium-Sized Enterprises in the Context of the Space Age - Ramírez-Blacio, Anita Maribel; Briones-Kusactay, Víctor Hugo; Contreras-Peña, María Fernanda; Bravo-Santos, Olga Marisol; Vega-Granda, Ricardo Alfredo; Avilés-Almeida, Pedro Alexander; Parrales-Escalante, Simón Bolívar; Casanueva-Yánez, Galvarino; Poveda-Burgos, Guido Homero Poveda-Burgos (Journal of Posthumanism, 2025)
The growing global space economy presents significant opportunities for small and medium-sized enterprises (SMEs) in Latin America. This article explores how Latin American SMEs can be integrated into the spatial value chain, taking advantage of market expansion, digitalization and international partnerships. Through an analysis of public policies, market trends and success stories, strategies are identified for SMEs to participate in sectors such as component manufacturing, satellite data services and Internet of Things (IoT) applications.